The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.5812/aapm.98679
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Comprehensive Pain Management Training Program on Awareness and Attitude of ICU Nurses

Abstract: Background: Pain is one of the main complaints of many patients in intensive care units. However, most nurses and physicians are unable to properly monitor and relieve pain in these patients. Factors such as patients' inability to describe their pain and insufficient knowledge of nurses and physicians have made pain management difficult. Given that the knowledge and attitude of nurses play an important role in the effective implementation of the pain management process, this study aimed to investigate the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
(53 reference statements)
0
5
1
Order By: Relevance
“…However, the knowledge levels of the two groups were comparable post-intervention, suggesting the effectiveness of the intervention. This finding contrasts with previous studies [ 46 , 47 ] that reported that nurses’ educational levels were not significant factors. These inconsistent results could be attributed to differences in the samples’ demographic characteristics.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the knowledge levels of the two groups were comparable post-intervention, suggesting the effectiveness of the intervention. This finding contrasts with previous studies [ 46 , 47 ] that reported that nurses’ educational levels were not significant factors. These inconsistent results could be attributed to differences in the samples’ demographic characteristics.…”
Section: Discussioncontrasting
confidence: 99%
“…These inconsistent results could be attributed to differences in the samples’ demographic characteristics. More than two-thirds of the nurses in this study were diploma holders, whereas most nurses in other studies had bachelor’s or master’s degrees [ 46 , 47 ]. Therefore, the current study findings highlight the importance of providing educational pain management programs for nurses with diplomas.…”
Section: Discussionmentioning
confidence: 75%
“…Pain assessment is said to be at the top level in proper pain relief and an important goal in patients' care. Because pain is one of the main experiences that might keep a patient comfortable, maintaining an optimal degree of comfort for critically ill patients is the universal goal for healthcare providers (Sedighie et al, 2020).…”
Section: Odasso Et Al 2021)mentioning
confidence: 99%
“…Mechanical ventilation for more than two days is the other cause of ARDS in patients who are admitted to the intensive care unit (ICU) (2). Studies have shown that patients who wean off later from mechan-ical ventilation have a higher rate of ventilator-associated pneumonia (VAP), lung damage, and mortality, which impose more costs on the health system (3)(4)(5)(6)(7)(8)(9)(10)(11). The presence of fibrin mesh in the air sac and fibrin accumulation in pulmonary capillaries and venules demonstrate an inflammatory process, which leads to ARDS development (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%